Wendy and Min: A Theatrical Response to British Chinese Acculturation, Identity and Cultural Hybridity - SUET KON (2024)
This PhD thesis comprises two components. The first part, Wendy and Min, represents the creative practice, a theatrical play dramatising the lives of the under-represented, diverse British Chinese community. The play explores inter-generational tensions arising from different degrees of acculturation and assimilation, cultural identity, and hybridity, as well as intra-racial tensions, intra-racial hierarchies, and intra-ethnic othering. The second part is a supporting essay divided into four main sections. The essay provides historical context for the play and offers a historical review of the settlement of the Chinese in Britain and the representation of the British Chinese on stage. In addition, it details a review of dramatic and literary sources that helped shape artistic decisions in the play’s plot, characterisation, dramatic structure, and style. Wendy and Min uses a character-driven, three-generation structure to interrogate the tensions arising from different degrees of generational acculturation and assimilation. The grandparents are first-generation immigrants from Hong Kong and Singapore/Malaysia. The second-generation parents are British-born or substantially brought up in the UK. The daughters, Wendy and Lisa are third-generation and British-born. Using the setting of a wedding and its various rituals, the play examines how different degrees of acculturation create ambiguity and fluidity in the British Chinese identity and how it is negotiated and articulated within the family when Wendy (Min), the protagonist, chooses to marry Peter, a mainland Chinese PhD student. Given the diversity of the British Chinese community, my own experience as a second- generation British-born Chinese of Malaysian descent living in Singapore would have been insufficient to create authentic, complex, and compelling characters. I did not want to resort to mythical, stereotypical, or hackneyed representations. I wanted to create characters that were contemporary and real and resonated with the audience. Therefore, in creating Wendy and Min in addition to my personal experience and those of my family and friends, I also used historical, social, and cultural studies, social media, anecdotal evidence, radio and informal interviews, and historical and contemporary British Chinese literary and dramatic works. This comprehensive approach detailed in the supporting essay gives me some confidence that although the creative piece is fictional, my myriad artistic choices are grounded in substance. In this way, I hope to create a piece that offers a more nuanced and complex representation of the British Chinese community, specifically, the second and third-generation British Chinese whose narratives are under-represented and seldom documented.